Etika Relasional dan Ketekunan Spiritual sebagai Kerangka Pembentukan Diri dalam Al-Qur’an: Telaah Surah al-Ḥujurāt [49]:11–12 dan al-ʻAnkabūt [29]:69 - Athma Mahmuda Damanik; Muhammad Jamil; Abu Sahrin (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
Studies on self-formation within the Qur’an often separate relational ethics from spiritual perseverance, leaving the connection between social discipline and internal transformation incompletely understood. This research analyzes the construction of relational ethics, spiritual perseverance, their relationship, and the process of self-formation as presented in QS. al-Ḥujurāt [49]:11–12 and QS. al-ʻAnkabūt [29]:69. A qualitative, library-based approach was employed, utilizing these two sets of verses as primary data sources—supported by classical and contemporary exegesis and relevant academic literature—and analyzed through a thematic-analytical method that considers the verses’ contexts, key terms, exegetical interpretations, inter-conceptual relationships, and arguments regarding self-formation. The study reveals that QS. al-Ḥujurāt [49]:11–12 shapes relational ethics by curbing behaviors such as belittling, disparagement, labeling, prejudice, fault-finding, and backbiting, thereby establishing ego discipline within social life. Meanwhile, QS. al-ʻAnkabūt [29]:69 fosters spiritual perseverance through the concept of jāhadū fīnā—a sustained earnestness in facing trials and seeking God’s guidance. The interplay between these elements creates a framework for self-formation characterized by the control of destructive tendencies, moral discipline, spiritual resilience, and a transcendental orientation. Self-formation unfolds gradually and reflectively as a continuous process of discipline that integrates internal qualities, relational conduct, steadfastness in trials, and the pursuit of divine guidance, rather than constituting an instantaneous inner transformation or mere normative compliance. These findings expand the scope of Qur’anic studies by offering an integrative reading that positions social ethics and spirituality as mutually reinforcing dimensions of self-formation.